Mangosteen (Garcia mangostana) Pericarp and alugbati (Basella rubra L) dyes as alternative to synthetic N3 dye in DSSCS - Cleofas, Maria Eliza A. (Animo Repository, 2017)
Dye Sensitized Solar Cells (DSSCs) are one of the emerging photovoltaic (PV) innovations which provide low cost, non-toxic and efficient energy. This research ventures into cheap natural dyes using mangosteen and alugbati as substitutes to expensive ruthenium complexes. This study aims to determine the best combination of four parameters sensitizing dye, copigment, dye pH, and metal dopant ratio that would yield the highest attainable power output. The study made use of pH values 1.5, 2.5 and 2.5, ferulic acid and sinapic acid as copigments for anthocyanin stabilization against color degradation, and Fe and Ni as metal dopants. The Taguchi method of orthogonal arrays was used for the experimental design and ANOVA for the statistical analysis. The best performing anthocyanin-based DSSC fabricated in this study works at an efficiency of 0.23% which corresponds to a maximum power output of 0.1166 W/m2. This optimum setup used pure alugbati as the anthocyanin source, ferulic acid as the copigment, an equal ratio of iron and nickel as metal dopants, and had a pH of 2.5. Meanwhile, the best performing N3-sensitized cell works at an efficiency of 0.448% which corresponds to a maximum power output of 0.2249 W/m2 and parameter combination of: N3, ferulic acid, iron and nickel, and 2.5. The maximum power output and efficiencies yielded in using anthocyanin from alugbati may not be comparable to those in using N3 however, the use of alugbati and mangosteen as sensitizer dye source is proven to be feasible. Although the mangosteen extract had a higher absorbance at the 400-430 nm region, the alugbati extract had more peaks throughout the visible spectrum and thus resulted in a higher DSSC efficiency. The addition of copigment and lowering of pH resulted in more peak absorbances. The copigment, dye pH, and metal dopant ratio for the best performing natural and N3-based DSSC were the same which indicates good interaction among ferulic acid, Fe:Ni dopant and a pH of 2.5. Combining iron and nickel as metal dopants resulted in a synergistic effect of lowering the band gap energy in the photoanode thus, yielding higher cell efficiencies.